Intra-erythrocytic vacuoles in asplenic patients: elusive genesis and original clearance of unique organelles - Dumas, Lucie; Roussel, Camille; Buffet, Pierre (Frontiers in Physiology, 2023)
The spleen plays a dual role of immune response and the filtration of red blood cells (RBC), the latter function being performed within the unique microcirculatory architecture of the red pulp. The red pulp filters and eliminates senescent and pathological RBC and can expell intra-erythrocytic rigid bodies through the so-called pitting mechanism. The loss of splenic function increases the risk of infections, thromboembolism, and hematological malignancies. However, current diagnostic tests such as quantification of Howell-Jolly Bodies and splenic scintigraphy lack sensitivity or are logistically demanding. Although not widely available in medical practice, the quantification of RBC containing vacuoles, i.e., pocked RBC, is a highly sensitive and specific marker for hyposplenism. The peripheral blood of hypo/asplenic individuals contains up to 80% RBC with vacuoles, whereas these pocked RBC account for less than 4% of RBC in healthy subjects. Despite their value as a spleen function test, intraerythrocytic vacuoles have received relatively limited attention so far, and little is known about their origin, content, and clearance. We provide an overview of the current knowledge regarding possible origins and mechanisms of elimination, as well as the potential function of these unique and original organelles observed in otherwise “empty” mature RBC. We highlight the need for further research on pocked RBC, particularly regarding their potential function and specific markers for easy counting and sorting, which are prerequisites for functional studies and wider application in medical practice.